Late presentation of developmental dysplasia of the hip: a 15-year observational study. (September 2017) - Talbot, C.; Adam, J.; Paton, R.
Abstract : Aims: Despite the presence of screening programmes, infants continue to present with late developmental dysplasia of the hip (DDH), the impact of which is significant. The aim of this study was to assess infants with late presenting dislocation of the hip despite universal clinical neonatal and selective ultrasound screening. Patients and Methods: Between 01 January 1997 to 31 December 2011, a prospective, longitudinal study was undertaken of a cohort of 64 670 live births. Late presenting dislocation was defined as presentation after three months of age. Diagnosis was confirmed by ultrasound and plain radiography. Patient demographics, referral type, reason for referral, risk factors (breech presentation/strong family history) and clinical and radiological findings were recorded. Results: There were 31 infants with an irreducible dislocation of the hip, an incidence of 0.48 (95% confidence interval (CI) 0.34 to 0.68) per 1000 live births. Of these, 18 (0.28 (95% CI 0.17 to 0.44) per 1000 live births; 58%) presented late. All infants had a documented normal newborn clinical examination and no abnormality reported in the six to eight week check. Of the 18 late presenting cases 72% (n = 13) had no risk factors: 16 were referred by GPs and two were late due to administrative issues (missed appointments). The mean time to diagnosis was 62.4 weeks (19 to 84). Conclusion: Despite universal clinical neonatal and selective ultrasound screening, late cases of irreducible hip dislocation still occur. We recommend an update of the national screening programme for DDH, a review of training and education of healthcare professionals involved in the physical examination of neonates and infants, and the addition of a further assessment after the six to eight week check. Cite this article: Bone Joint J 2017;99-B:1250–5.